The Effect of LDR, Bopo, NPL, and NIM on Roa at Bank Perekonomian Rakyat Bank Kota Bogor for the Period 2016–2024 - Asmara, Anjas; Taufiqurrochman, Cecep (Publikasi Indonesia, 2026)
Background: This study aims to analyze the influence of financial ratios on the profitability of Bank Perekonomian Rakyat (BPR) Bank Kota Bogor during the period 2016–2024. Profitability, measured using Return on Assets (ROA), is influenced by the Loan to Deposit Ratio (LDR), Operational Costs to Operating Income Ratio (BOPO), Non-Performing Loans (NPL), and Net Interest Margin (NIM). Objective: This study aims to examine and analyze the effect of LDR, BOPO, NPL, and NIM on the ROA of BPR Bank Kota Bogor, both simultaneously and partially. Methods: This research uses a quantitative approach with multiple linear regression analysis. The data used is secondary data from the annual financial statements of BPR Bank Kota Bogor from 2016 to 2024. Results: The results show that, simultaneously, LDR, BOPO, NPL, and NIM significantly affect ROA. Partially, NPL and BOPO negatively affect ROA, while LDR and NIM positively affect ROA. Conclusion: This study contributes to understanding the factors influencing BPR profitability and provides practical recommendations for the management of BPR Bank Kota Bogor to improve financial performance in the future.